2006
DOI: 10.1007/s00244-003-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Mobilization from Acidic Forest Soils in Leigongshan Area, Southwestern China: Laboratory and Field Study

Abstract: Abstract. Aluminium mobilization from acidic forest soils in the remote Leigongshan area in southwestern China was investigated in the field and by a laboratory batch experiment using sequential extractions with HCl solutions with pH of approximately 3.4. Experimental data showed that strongly organically bound aluminium (Alp-Alcu) decreased significantly after sequential extraction, whereas exchangeable aluminium (Alex) increased in all three horizons. In the A-horizon with higher base saturation (BS), dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The non-crystalline inorganic Al and the highly stable organoaluminium complexes were not correlated with the dissolved Al. Some authors consider that highly stable organoaluminium complexes are the principal source of soluble aluminium, while exchangeable Al regulates Al solubility during soil acidification processes (Guo et al 2006). However, in the present study, the organic matter appeared to play an important role in withdrawing Al from the solution and fixing it in the highly stable complexes, which are more abundant in the rhizospheric zone.…”
Section: Aqueous Aluminiummentioning
confidence: 64%
“…The non-crystalline inorganic Al and the highly stable organoaluminium complexes were not correlated with the dissolved Al. Some authors consider that highly stable organoaluminium complexes are the principal source of soluble aluminium, while exchangeable Al regulates Al solubility during soil acidification processes (Guo et al 2006). However, in the present study, the organic matter appeared to play an important role in withdrawing Al from the solution and fixing it in the highly stable complexes, which are more abundant in the rhizospheric zone.…”
Section: Aqueous Aluminiummentioning
confidence: 64%
“…This means that higher AlS and lower BS will increase the Al concentration in soil solution. Guo et al (2006) showed that in soils with lower AlS and higher BS, more mobilized Al was retained in soil as exchangeable Al. With the (Fig.…”
Section: Pls Regression Analysismentioning
confidence: 99%
“…Elevated Al concentrations in soils, streams and lakes is a potential threat to both terrestrial and aquatic organisms due to the toxicity of certain Al species (Driscoll et al, 1980;Andersson, 1988). In China, high Al concentrations induced by acid deposition have also been reported (see Guo et al, 2006;Xue et al, 2003). Based on laboratory experiments and limited field monitoring, the significance of some possible influencing factors have been documented by several specific studies (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Leaching and batch experiments were used by e.g. Guo et al (2006) and Bohan et al (1997Bohan et al ( , 1998. Solutions acidified via mineral acids (H 2 SO 4 , HNO 3 , HCl) up to approximately 3.5 pH are usually used as leaching media.…”
mentioning
confidence: 99%
“…Solutions acidified via mineral acids (H 2 SO 4 , HNO 3 , HCl) up to approximately 3.5 pH are usually used as leaching media. Guo et al (2006) concluded that strongly organically bound Al is the main source of aqueous Al, whereas exchangeable Al plays an important role in regulating Al solubility during soil acidification. Soil organic carbon and soil water pH are considered as the key factors in Al release determination.…”
mentioning
confidence: 99%